Does plumage colour signal fitness in the tawny owl Strix aluco?. (12th February 2021) - Solonen, Tapio
Abstract : Plumage colour has been hypothesized to signal fitness in its component parts survival and reproduction. In the tawny owl Strix aluco, grey individuals have been considered to be more viable and productive than brown ones in cold environmental conditions. The recent increase in the frequency of the brown morph in Finland has been explained by the climate warming. However, in recent decades there have been no trends in the general mildness of winters. Therefore, trends in the abundance of owls due to climate warming per se were unexpected. In a population near the southern coast of Finland, the abundance of grey (not brown) individuals increased significantly during the period 1986–2018, suggesting that natural selection has recently favoured the grey colour morph. During snowy and cold winters grey owls seemed to survive better than brown ones, suggesting that plumage colour signals adaptations to winter weather. The proportion of brown individuals in each year was best explained by the joint effect of snow cover and winter temperature. Extreme peaks in snow fall and cold winters seemed to affect substantially and rather similarly the abundance of both colour morphs. Between population differences in the occurrence of colour morphs were probably due to local and temporal differences in the snow cover. The number of fledglings was significantly related to the colour morph and weather conditions of the preceding winter in males but not in females. This suggests that coloration of males signals fitness in reproduction.